2022
DOI: 10.2147/dmso.s383098
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Composition with Pulmonary Function in Ningxia: The China Northwest Cohort

Abstract: Background In recent decades, obesity has become an epidemic worldwide and is a risk factor for many chronic diseases. Lung function is also a predictor of various chronic diseases. However, research results on the association between obesity and lung function are inconsistent and few studies have evaluated the association between central obesity indicators and lung function. Therefore, this study explored the correlation between central obesity and lung function. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…First, the normal population has a BMI of 18.5–24, which has no significant impact on the pulmonary function. Second, those who are overweight or obese have a close association with the PF [ 22 , 23 ]. Third, our findings demonstrated that when the BMI was less than 18.5, a positive correlation with PF was observed for the BMI.…”
Section: Discussionmentioning
confidence: 99%
“…First, the normal population has a BMI of 18.5–24, which has no significant impact on the pulmonary function. Second, those who are overweight or obese have a close association with the PF [ 22 , 23 ]. Third, our findings demonstrated that when the BMI was less than 18.5, a positive correlation with PF was observed for the BMI.…”
Section: Discussionmentioning
confidence: 99%
“…According to the [21], over half of the British population were said to be overweight between 1980 and 1995, the prevalence of obesity in Britain also doubled from 8% to 15% in 2016, in fact it was projected that by 2050, 15% and 62% of females in social class I and class V will be obese [22]. Most of South America and parts of Asia reported it at 16.4% from 2015 to 2019 in China [23]. Country-wise according to the world population review, the highest obesity prevalence was recorded in countries such as Nauru 61%, Cook Island 55.9%, Palau 55.3%, Kuwait 37.9%.…”
Section: Global Epidemiology Of Obesitymentioning
confidence: 99%
“…Obesity especially central obesity restricts lung compliance function due to diaphragm-reduced movement (expansion-relaxation function) which eventually limits the respiratory functional capacity of the lungs leading to decreased lung function i.e. FVC and FEV1 in people with central obesity than when compared to the normal population [23]. An alternative possible mechanism is a reduction in the functional pulmonary capacity due to increased deposition of adipose tissues in the pulmonary compartment and respiratory-supporting tissues such as in the abdomen and surrounding viscera [61].…”
Section: Obesity -Recent Insights and Therapeutic Optionsmentioning
confidence: 99%
“…The BIA method is used in healthcare to evaluate obesity, although it is rarely associated with impaired lung function. Studies relating BIA to impaired lung function are relatively few; still, they have shown a negative association with lung function (29,30).…”
Section: Introductionmentioning
confidence: 99%